2018
DOI: 10.1080/14767058.2018.1481384
|View full text |Cite
|
Sign up to set email alerts
|

Maxillo–occipital line: a sonographic marker for screening of open spina bifida in the first trimester of pregnancy

Abstract: Maxillo-occipital line is an easy addition to the evaluation of first-trimester screening of open spina bifida. Further studies are needed to determine the false-positive and false-negative rates of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…A previously published study evaluating the MO line has shown excellent results with detection of 100% of spina bifida cases and no false positives . In our study, all but one case with sacral open spina bifida had an abnormal MO line (false positive 0.1%).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…A previously published study evaluating the MO line has shown excellent results with detection of 100% of spina bifida cases and no false positives . In our study, all but one case with sacral open spina bifida had an abnormal MO line (false positive 0.1%).…”
Section: Discussionmentioning
confidence: 93%
“…On a sagittal view of the fetal head, measurements of the IT, BS, and BSOB were obtained on the stored images according to the original description by their authors (Figure ). The ratio between the BS and the BSOB was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations